1973
DOI: 10.1037/h0034004
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control among opiate addicts.

Abstract: Because the use of opiates enables the user to exert direct control over reinforcements, opiate addicts were predicted to show strongly internal expectancies on Rotter's Internal-External Locus of Control scale, especially on items referring directly to "personal control." Item and total score differences between 600 hospitalized addicts (balanced for sex and race) and a comparison group of 800 college Ss (white, balanced for sex) strongly supported the predictions. Multivariate analyses of addict subgroups di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Several authors have demonstrated a high internal level of control in heroin addicts (e.g. Calicchia, 1974;Berzins & Ross, 1973). Their rationale is similar to that for similar findings in alcoholic populations (e.g.…”
mentioning
confidence: 75%
“…Several authors have demonstrated a high internal level of control in heroin addicts (e.g. Calicchia, 1974;Berzins & Ross, 1973). Their rationale is similar to that for similar findings in alcoholic populations (e.g.…”
mentioning
confidence: 75%
“…Male Addict Patients -U S A . (Berzins and Ross, 1973) First Year female undergraduates unable to relate in interpersonal situations (Dua, 1970) 1. Pre-test 2.…”
Section: Hong Kong Studentsmentioning
confidence: 99%
“…No significant differences were found among the diagnostic groups with respect to personal expectancies of control as measured by the PLC subscale. The PLC subscale scores reported correspond to the collegiate sample in a Berzins and Ross (1973) study and the more impaired psychiatric samples in a Camargo and Reznikoff (1975) study.…”
Section: Discussionmentioning
confidence: 66%
“…Mirels (1970) in an attempt to clarify the factor structure of the I-E scale, identified two item clusters: One that deals with belief in the control of personal destiny and another that deals with belief in individual influence over sociopolitical forces. Berzins and Ross (1973), who utilized these item clusters as subscales in a study of locus of control among opiate addicts, found an opiate addict group more internal than a student group for full scale I-E scores as well as on a personal locus of control subscale (PLC) scores. Abramowitz (1973) SLC subscales were uiicorrelated and suggested that political commitment could be predicted by the sociopolitical subscale.…”
mentioning
confidence: 99%